DNA Replication – A Unique Orchestration of Actions of Proteins - MANDAL, JAYDIP (SCHOOL SCIENCE, 2007)
WATSON AND Crick’s landmark discovery of DNA structure in April 1953 suggested how DNA might be replicated and preserved for hundreds of generations. The self complementarity of two poly nueleotide strands of a DNA double helix discarded the idea that protein template might play a role in DNA replication. The semiconservative fashion of DNA replication was distinctively demonstrated by Matthew Meselson and Franklin Stahlin 1958. This clearly states that when one DNA molecule duplicates to produce two identical new DNA molecules, each of the new molecules is comprised of one polynucleotide strand from the original DNA molecule bonded to one newly synthesised polynucleotide strand.